MALFORMACIÓN ARTERIOVENOSA UTERINA: REPORTE DE UN CASO - Saldaña Vargas, Roy Arnold (2025)
A 36-year-old woman with a history of cesarean section and uterine curettage, who presented with persistent abnormal uterine bleeding and severe anemia. Transvaginal Doppler ultrasound revealed multiple serpiginous vascular spaces within the myometrium, showing turbulent high-velocity and low-resistance flow, findings compatible with an acquired uterine arteriovenous malformation. Due to the high risk of rebleeding and no desire for future fertility, a total abdominal hysterectomy was performed. The diagnosis was confirmed by histopathological examination. The patient had a favorable postoperative course and was discharged without complications. This case highlights the value of Doppler ultrasound as a first-line diagnostic tool, particularly in women with a history of invasive uterine procedures. Early clinical suspicion and an individualized therapeutic approach are essential to prevent adverse outcomes in this rare but potentially life-threatening condition.